2016
DOI: 10.1111/btp.12288
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Dynamics and the Effects of Biotic and Abiotic Factors on Plant Physiognomic Groups in a Hurricane‐impacted Lower Montane Tropical Forest

Abstract: We assessed the short‐term effects of biotic (density, plant size) and abiotic factors (light), on the dynamics of physiognomically different plant groups (palms, tree ferns, lianas, and trees) in a hurricane‐impacted tropical wet montane forest, John Crow Mountains, Jamaica. All plants ≥2 cm (dbh) found within 45, 25 × 25 m permanent sample plots (2.8125 ha), established according to a randomized block design along an elevation gradient, were tagged and measured (dbh) in 2006 and re‐assessed in 2012 after Hur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…, Luke et al . ). If differences in vegetation were an important driver mediating forest responses in our study sites, however, we would expect larger differences between elevations within each island (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Luke et al . ). If differences in vegetation were an important driver mediating forest responses in our study sites, however, we would expect larger differences between elevations within each island (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The number of plots sampled was relatively small, but additional analyses suggested that our conclusions would not have altered substantially if more plots were sampled (Appendix S1). Previous studies have noted how differences in vegetation may mediate forest responses to hurricanes (Carrington et al 2015, Luke et al 2016b). If differences in vegetation were an important driver mediating forest responses in our study sites, however, we would expect larger differences between elevations within each island (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar processes as described above for ferns have likely affected sapling demographics in the control relative to canopy trimmed plots (Luke et al, 2016;Royo et al, 2011). In 2017 at the time of Hurricane Maria, there could have been more seeds in the soil seed bank and seedlings in the seedling bank of the control plots, which had not already grown to sapling stage than in trimmed, hurricane simulation plots.…”
Section: Simulated Versus Natural Hurricane Responsesmentioning
confidence: 83%
“…Similarly, accumulated seeds of pioneer species would germinate and grow quickly to reach sapling size, being recorded as recruits in the post‐Maria tree census. In all of the plots—the hurricane simulation plots with two canopy trims and a hurricane, and the control plots with only one hurricane impact—sapling densities will decline as the canopy closes and reduces light, causing shade‐induced mortality of pioneer species, and density‐dependent mortality for abundant shade‐tolerant species (Comita, Uriarte, Thompson, et al, 2009; Comita, Uriarte, Forero‐Montaña, et al, 2018; Luke et al, 2016; Muscarella et al, 2013; Royo et al, 2011; Uriarte et al, 2018). Compositional shifts toward more pioneer and secondary‐successional species in the CTE may be partly due to increased throughfall and wetter soils in the trimmed plots, with soil VWC being >0.1 cm 3 water/cm 3 soil wetter in trimmed plots (Appendix S1: Figure S2; Van Beusekom et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As such, turnover at the stand-level for the JCM was within the range of values for the BM after Gilbert made landfall, but higher than the BM during a period that overlapped, when three hurricanes passed closed to the island. Additionally, 25-50% of trees 2-10 cm in DBH died during the period 2006-2012 in the JCM (Luke et al 2016b), likely removing some of the trees recruited since Hurricane Gilbert (and before). Moreover, in the BM, the mortality of damaged trees was 2-8 times higher than undamaged stems 19 years after Gilbert (Tanner et al 2014).…”
Section: The Impact Of Legacy Hurricanes On Stand-level Spatiotemporal Diversity and Density Patternsmentioning
confidence: 99%